Analysis of Molecular Docking and Dynamics Simulation of Mahogany (Swietenia macrophylla King) Compounds Against the PLpro Enzyme SARS-COV-2 - Lalu Sanik Wahyu Fadil Amrulloh; Nuraini Harmastuti; Andri Prasetiyo; Rina Herowati (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Using natural ingredients as antivirals can be considered a treatment for SARS-CoV-2. One of the potential plants, mahogany (Swietenia macrophylla King), is widely used in various countries as an antiviral treatment. Paparin-like protease (PLpro) is an essential cysteine "‹"‹protease that regulates viral replication and interferes with the regulation of immune sensing. Objective: This study aims to predict which compounds in the mahogany plant have good affinity, patterns, and stability interaction against the target protein of SARS-CoV-2. Methods: The drug-likeness parameter using SwissADME was used to screen compounds that will be docked against PLpro using the Autodock program. The parameters observed in molecular docking analysis are the value of bond energy and interaction model to amino acid residues. The compounds in mahogany plants that have the best interactions were then analyzed using molecular dynamics simulation methods to determine the stability of their bonds based on the values of Root Mean Square Deviation (RMSD) and Root Mean Square Fluctuation (RMSF). Results: Twenty-two compounds met the drug-likeness requirements. Molecular docking analysis showed that the compounds predicted to have the best binding affinity and have an interaction pattern similar to natural ligands towards the molecular target of PLpro are 7-deacetoxy-7-oxogedunin and 3β-hydroxy-stigmast-5-en-7-one. The molecular dynamics simulation results revealed that based on the RMSD and RMSF values, the compound 3β-hydroxy-stigmast-5-en-7-one showed higher stability than 7-deacetoxy-7-oxogedunin. Conclusion: 3β-hydroxy-stigmast-5-en-7-one and 7-deacetoxy-7-oxogedunin were predicted to have good interaction with PLPro; however, 3β-hydroxy-stigmast-5-en-7-one showed the higher interaction stability.